Evaluation and Design of Application Interface Design Mitrajual uses the Double Diamond Method at PT. Mitrajual Indonesia Jaya - Eka Hirinda Zulfa; Tri Sagirani; Vivine Nurcahyawati (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2022)
PT. Mitrajual Indonesia Jaya is one of the growing e-commerce companies in Indonesia. This company sells various kinds of electronic goods and household appliances. In March 2019, the company released the Mitrajual app. Based on the results of interviews that have been conducted, the results show that the Mitrajual application already has several features, and already has several application users. However, several things become obstacles when using the application. The initial evaluation was carried out using indicators of learnability, efficiency, memorability, errors, satisfaction. From the results of the initial evaluation, the average overall indicator has a mean of 2.07, which means that the appearance of the Mitrajual application is not good. Based on the problems that have been described, a solution is needed to evaluate and design the interface design using the Double Diamond and Usability Testing method. The result of this research is a user interface. The results of the evaluation of the new design on average have a mean of 3.54 so that the comparison of the mean with the old design is 1.45 which can be said to have a significant difference. The results after iterations have an average overall mean indicator of 3.84 which can be said to be very good. So, it can be concluded that the design of the recommended solution provided is acceptable to users in terms of usability